HUBUNGAN KEPERCAYAAN DIRI SISWA DENGAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA KELAS IV DI SDN CIPONDOH 8 - Ayu Wahyuni; Asih Rosnaningsih; Yoyoh Fathurrohmah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The relationship between students' self-confidence and the English speaking skills of grade IV students at SDN Cipondoh 8. This study aims to determine the relationship between students' self-confidence and the English speaking skills of grade IV students at SDN Cipondoh 8. This research is a quantitative study using a survey method. The population in this study were the fourth grade students at SDN Cipondoh 8 in 2 classes with a total of 52 students. The sample in this study were 20 students using the Random Sampling Technique. Data collection was carried out using an instrument in the form of a self-confidence questionnaire with a Likert scale model and an English speaking skill test. Data analysis in this study used simple linear regression. The results of this study indicate that there is a positive and significant relationship between students' self-confidence and the English speaking skills of fourth-grade students at SDN Cipondoh 8, with an r count or Pearson correlation of 0.530 with a significance value of 0.016, which means that if students' self-confidence is higher, the the better the English speaking skills of grade IV students at SDN Cipondoh 8, and vice versa. This is also evidenced by the coefficient of determination obtained which is equal to 28.1% and the remaining 71.9% is influenced by other factors, such as interest, motivation, etc.